Ras complements the carboxyl terminus of v-Abl protein in lymphoid transformation. - Parmar, K (1996)
Abelson murine leukemia virus (Ab-MLV) mutants expressing v-Abl proteins lacking the carboxyl terminus are compromised in the ability to transform lymphoid but not NIH 3T3 cells. This feature correlates with the presence of low levels of phosphotyrosine in lymphoid cells infected with carboxyl-terminal truncation mutants. In contrast, high levels of phosphotyrosine are observed in NIH 3T3 cells infected with wild-type and mutant Ab-MLV. Two downstream targets affected in lymphoid transformants are the GTPase-activating protein and GTPase-activating protein-associated protein p62, molecules which are heavily tyrosine phosphorylated in lymphoid cells transformed by wild-type Ab-MLV but not carboxyl-terminal truncation mutants of Ab-MLV. This difference suggested that signaling mediated via the Ras pathway may be compromised in lymphoid cells expressing the carboxyl-terminal truncation mutants. Consistent with this idea, expression of v-Ha-ras complemented these mutants in primary bone marrow transformation assays and increased transformation frequencies obtained with the Ab-MLV mutants 8- to 20-fold. These data suggest that a biologically important link exists between the carboxyl terminus of v-Abl protein and the Ras pathway. Signals transmitted via this connection may enhance those mediated via other regions of the v-Abl protein and facilitate transformation of primary, nonimmortalized cells such as pre-B lymphocytes.